The impact of different left ventricular geometric patterns on right ventricular deformation and function in the elderly with hypertension: A two-dimensional speckle tracking and three-dimensional echocardiographic study - Xue, Jiping; Kang, Xiaoyan; Qin, Qin; Miao, Junwang; Li, Shuai; Kang, Chunsong (Frontiers in Cardiovascular Medicine, 2022)
Objective This study aimed to evaluate the impact of different left ventricular geometric patterns on right ventricular deformation and function in the elderly with essential hypertension via two-dimensional speckle tracking and three-dimensional echocardiography. Methods A total of 248 elderly people with essential hypertension were divided into four groups based on the left ventricular mass index (LVMI) and relative wall thickness (RWT): the normal geometric, concentric remodeling, eccentric hypertrophy, and concentric hypertrophy groups. Moreover, 71 participants were recruited as the control group. These participants were examined by two-dimensional speckle tracking and three-dimensional echocardiography to obtain the right ventricular strain parameters, three-dimensional volume, and function parameters. Results The right ventricular strain parameters decreased gradually from the normal geometric group to the concentric hypertrophy group (P < 0.05), and the strain parameters in the concentric remodeling, eccentric hypertrophy, and concentric hypertrophy groups were lower than those in the control and normal geometric groups (P < 0.05). The right ventricular three-dimensional echocardiographic parameters only changed in the eccentric hypertrophy group (P < 0.05) and the concentric hypertrophy group (P < 0.05) in the form of an increase in volume and a decrease in function. Multivariate linear regression analysis showed that the right ventricular free wall longitudinal strain was independently associated with the systolic blood pressure (SBP), LVMI, and RWT (P < 0.05) and was primarily affected by the LVMI (normalized β = 0.637, P < 0.05). Conclusion The systolic function of the right ventricular myocardium declined in the elderly with essential hypertension due to impaired myocardial mechanics. The right ventricular strain parameters could indicate mechanical damage in the concentric remodeling group earlier than the right ventricular three-dimensional volume and function parameters. The right ventricular free wall longitudinal strain was primarily subject to the LVMI.